A Comparison of Perceptions of Factors in the Job Accommodation Process Among Employees With Disabilities, Employers, and Service Providers. (April 2013) - Dong, Shengli; Oire, Spalatin N.; MacDonald-Wilson, Kim L.; Fabian, Ellen S.
Job accommodation is a multifaceted and interactive process. Stakeholder groups (i.e., employees with disabilities, employers, and in some cases service providers) make decisions about requesting or providing job accommodations based on multiple factors in this process. An understanding of stakeholder differences in their perceptions of these factors may mitigate the myths and misconceptions about accommodations, and facilitate the accommodation process. Stakeholder perspectives on the importance of factors involved in the accommodation process are compared. How these perceptions may affect the likelihood of requesting or providing accommodations is discussed, along with the implications for rehabilitation professionals.